Analysis of Students’ Philanthropic Behavior: Driving and Inhibiting Factors to Participation in Social Activities on Campus - Sulastri Sulastri; Mas Fierna Janvierna Lusie Putri; Nurullita Sari; Pat Kurniati; Dwi Septipane (Yayasan Keluarga Guru Mandiri, 2025)
Philanthropic behavior among students is a salient indicator of civic awareness. This study analyzes how driving factors and inhibiting factors shape students' participation in campus-based social activities. Using a quantitative survey of 200 students from three Indonesian universities, we administered a 20-item Likert-scale questionnaire and analyzed the data using validity and reliability tests, Pearson correlations, and multiple linear regression (? = .05). All items demonstrated validity and reliability. Regression results indicate that driving factors have a positive and significant impact on philanthropic participation (? = 0.585, p .001), whereas inhibiting factors, such as time constraints and academic workload, do not significantly predict participation (? = –0.051, p = .404). The model explains 39% of the variance in participation (R² = 0.390), indicating that prosocial values, empathy, peer support, and campus community participation are more significant predictors than contextual constraints. These findings reinforce the Theory of Planned Behavior and the literature on prosocial development, underscoring the importance of intention and social norms in shaping behavior. We discuss implications for program design, including integrating community service into formal recognition systems, strengthening student-led initiatives, and ensuring sustained organizational regeneration to cultivate durable civic participation on campus.